Polymorphic gene markers ILRA and IL2: population distinctions in association with diabetes mellitus - Olga Igorevna Kopylova; Tamara Leonidovna Kuraeva; Elena Yur'evna Lavrikova; Elena Vital'evna Titovich; Aleksey Georgievich Nikitin; Valentina Alexandrovna Peterkova; Valery Vyacheslavovich Nosikov; Ivan Ivanovich Dedov (Сахарный диабет)
AIMS: In order to study type 1 diabetes mellitus associations, we conducted a comparative analysis of allele and genotype frequencydistribution of polymorphic markers rs41295061 and rs11594656 of IL2RA gene, which encodes α-chain of interleukin-2 receptor, - and rs2069762, a marker of IL2, gene, encoding interleukin-2. MATERIALS AND METHODS: Experimental group included 451 patients with type 1 diabetes mellitus (DM); control group consistedof 306 healthy subjects (both groups were represented by ethnic Russians). Alleles and polymorphic markers were identified byreal-time amplification method. RESULTS: A comparative analysis of patients with type 1 DM and healthy control group did not show statistically significant differencesfrom the viewpoint of allele and genotype frequency distribution of polymorphic markers rs41295061, rs11594656 and rs2069762. This makes Russian patients considerably different from European ones where markers in question show substantialassociation with type 1 DM. CONCLUSIONS: A comparative analysis of allele and genotype frequency distribution of IL2-RA and IL2 genes polymorphic markersshowed population differences in association of these markers in Russian and European patients.